Biolinguistics : exploring the biology of language - Jenkins, Lyle (Cambridge University Press, 2000)
This book investigates the nature of human language and its importance for the study of the mind. It considers language from a biological point of view and, uniquely, argues that genetic or biological endowment plays a more central role in language acquisition than instruction, learning, or cultural determinants.